Implementation of E-Book Services (Adkuh Book) For The Public At Surakarta Orthopedic Hospital - Herawati Prianggi; Dola Fitritha Raras Handayani; Nella Tri Surya; Devi Elvina Rachma; Nur Rachmat (MEDIA ILMU KESEHATAN, 2023)
Background: It is hoped that the use of e-Government from bureaucracy can be an alternative for bureaucratic reform for the better. The concept of digital public services leads to effective principles. while efficient means doing something correctly.Objective: To increase the convenience of health services by facilitating E-Book (Adkuh Book) services to the public.Method: This research method uses Research and Development which to produce certain products and test the effectiveness of these products. Both products can produce new products or modify existing products.Results: From the results of the bivariate analysis, it was found that there was an increase in respondents' interest (the average pre-test score with high interest was 96.78 points and the average post-test score with low scores was 43.04 points). To look for disease information before seeking treatment or registering at the Surakarta orthopedic hospital and was statistically significant (p=<0.001). Most respondents know how to access the Adkuh BookConclusion: There is a positive and significant influence on the intention to use the Adkuh Book on the use of health information for orthotic prosthetic patients. There is a positive and significant influence between Perceived Ease of Use on Intention to use Adkuh Book.